PROCESS CONTROL OF SACK PRODUCTION USING FAILURE MODE EFFECT ANALYSIS (FMEA) AND FAULT TREE ANALYSIS (FTA) METHODS - Dimas (Journal Knowledge Industrial Engineering (JKIE), 2023)
Work station. This study is a type of case study. The data collection technique used is to collect defective product data at each observation and documentation station. The data analysis technique used in this study is (1) collecting information about the number of defective products. (2) Processing the data to find out which sector has the most potential to cause product damage. (3) Analyzing the processed data using the FAILURE Mode Effect Analysis (FMEA) and Fault Tree Analysis (FTA) methods. The results of the study prove that FAILURE Mode Effect Analysis (FMEA) and Fault Tree Analysis (FTA) determine the SOD and RPN values derived from determining potential failure modes. This was obtained through field studies by looking directly at each work station that was a failure factor. in the production process, looking directly at the production process data for 1 month, then making a weighting table, Occurrence.